Encephalocele—radial, cardiac, gastrointestinal, anal/renal anomalies: Novel evidence for a new condition?. Issue 5 (19th March 2014) - Valdez, Carolina M.; Altmayer, Stephan P.L.; Barrow, McArthur A.; Telles, Jorge A.B.; Betat, Rosilene da S.; Zen, Paulo R.G.; Rosa, Rafael F.M.
<x xml:space="preserve">Abstract</x> The association between encephalocele and radial defects is considered uncommon. These features have been occasionally described separately in certain recurrent conditions such as VACTERL association, oculo‐auriculo‐vertebral spectrum and Edwards syndrome (trisomy 18). DK‐phocomelia is a rare syndrome characterized by both findings. However, Froster‐Iskenius and Meinecke [1992, Clin Dysmorphol 1: 37–41] and Kunze et al. [1992, Eur J Pediatr 151: 467–468] reported patients presenting similar malformations. We proposed, through the description of an additional case, that these last patients present the same condition and thus represent a new syndrome. The fetus presented a cranial vault deformity associated with an exuberant herniation of brain content, compatible with occipital encephalocele. Other uncommon features were also identified: microtia of the left ear with atresia of the external auditory canal; radial defect with aplasia of left radius and thumb; findings suggestive of a congenital heart defect and esophageal atresia; hypoplastic lungs and adrenals; thoracolumbar scoliosis; atrophic right kidney; and single umbilical artery. Thus, based on our review, we believe that these patients represent a new condition characterized by encephalocele and radial defects associated with multiple malformations. We propose, that the name "Encephalocele–radial, cardiac, gastrointestinal, anal/renal anomalies, " as suggested by the London Medical Database, or even the name, "Froster‐Iskenius and Meinecke syndrome" should be used to indicate these cases. © 2014 Wiley Periodicals, Inc.